2007
DOI: 10.1258/095646207780749763
|View full text |Cite
|
Sign up to set email alerts
|

HIV-infected children vaccination coverage and safety in a Western European cohort: a retrospective study

Abstract: Since the implementation of highly active antiretroviral therapy in HIV-infected children, response to scheduled vaccines may determinate future morbidity and mortality. The aims of this study have been to describe the current vaccine coverage, vaccine safety and concordance with vaccine recommendations of the 68 HIV-infected children and adolescents followed up in our Unit. Forty-four percent of the children received at least one dose of the oral polio vaccine (OPV). Only 9.1% needed and received a second set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…In France, two single‐centre studies reported vaccination rates of 21% and 31% among adult HIV‐positive patients. Another study from Spain focusing on HIV‐infected children reported that only 23% had a yearly influenza vaccination documented . Based on the available data, it appears that influenza vaccination rates among HIV‐positive patients in Europe are lower than in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…In France, two single‐centre studies reported vaccination rates of 21% and 31% among adult HIV‐positive patients. Another study from Spain focusing on HIV‐infected children reported that only 23% had a yearly influenza vaccination documented . Based on the available data, it appears that influenza vaccination rates among HIV‐positive patients in Europe are lower than in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…However, health care staff responsible for immunization delivery may miss opportunities for immunizing HIV-infected children because they are unaware of those recommendations, they are concerned about greater risk with use of vaccines in this population, or other reasons. African [4, 5] and European studies [6,7, 8] found lower immunization coverage of HIV-infected children compared to uninfected peers, while a North American study found equally low vaccine coverage, for both HIV-infected and the HIV-exposed uninfected populations for some vaccines [9]. In a rural South African population, maternal HIV-positive status was independently associated with lower vaccination rates for four vaccines in children 12–23 month of age (BCG, DTP3, poliomyelitis, and hepatitis B) [10].…”
mentioning
confidence: 99%
“…17 Despite HIV infected children are prone to infectious diseases and the protection of such vulnerable population should be undertaken, immunization reluctance is a widely phenomenon described also in other European studies. [10][11][12] This is partially due to the concerns regarding safety of vaccines, 18,19 especially with live-attenuated vaccines, in severely immunocompromised individuals. Moreover, the increase of HIV viral load after vaccination, as result of T-cell activation and proliferation, therefore disease progression, represents reason of hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Although these children represent an appropriate target group for immunization, the available data indicate suboptimal coverage rates, partially due to the physician uncertainty regarding the time-course of the immune reconstitution, the optimal timing of vaccination after starting HAART, and the safety profile in such patients. 5,[10][11][12] Moreover, for HIV-infected individuals, appropriate strategies are crucial for identifying those susceptible to preventable infections and prone to severe complications, and for ensuring them adequate protective immunity through the specific immunization schedules in terms of timing and number of vaccine doses rather than undergoing revaccination upon failure of immunization. 13 Background.…”
Section: Introductionmentioning
confidence: 99%